Sensory and metabolic profiles of "Fuji" apples (Malus domestica Borkh.) grown without synthetic agrochemicals: the role of ethylene production. Issue 12 (2nd December 2015) - Tanaka, Fukuyo; Miyazawa, Toshio; Okazaki, Keiki; Tatsuki, Miho; Ito, Tsutae
Abstract: Flavors of "Fuji" apple cultivated with or without synthetic agrochemicals were compared using quantitative descriptive analyses (QDA) and metabolite profiling for 3 seasons. Experimental plots included conventional crops (with agrochemicals) and organic crops (without agrochemicals) at our institute and organic and conventional farms. Additionally, mass market samples were analyzed. Organic apples were weak in sweetness and floral characteristics and had enhanced green and sour flavors. Most esters and sugars were present in lower concentrations in organic than in conventional apples. Close relation of principal component 1 of QDA and metabolite profiles, to ethylene production suggested that ethylene is considerably involved in flavor synthesis. Reduced ethylene associated with immaturity accounted for insufficient flavor synthesis and weak aroma and flavor attributes of organic apples. Furthermore, organic apples from the farm were more flavorsome than those from the institute in 2012, suggesting possible recovery of ethylene production after a long organic cultivation period. Abstract: : Organic "Fuji" apples, which were weak in sweet and floral characteristics and had lower levels of esters, were accounted for by smaller ethylene.